Intermittent Fasting Applied in Combination with Rotenone Treatment Exacerbates Dopamine Neurons Degeneration in Mice - Tatulli, Giuseppe; Mitro, Nico; Cannata, Stefano M.; Audano, Matteo; Caruso, Donatella; D’Arcangelo, Giovanna; Lettieri-Barbato, Daniele; Aquilano, Katia (Frontiers in Cellular Neuroscience, 2018)
Intermittent fasting (IF) was suggested to be a powerful nutritional strategy to prevent the onset of age-related neurodegenerative diseases associated with compromised brain bioenergetics. Whether the application of IF in combination with a mitochondrial insult could buffer the neurodegenerative process has never been explored yet. Herein, we defined the effects of IF in C57BL/6J mice treated once per 24h with rotenone (Rot) for 28 days. Rot is a neurotoxin that inhibits the mitochondrial complex I and causes dopamine neurons degeneration, thus reproducing the neurodegenerative process observed in Parkinson’s disease. IF (24h alternate-day fasting) was applied alone or in concomitance with Rot treatment (Rot/IF). IF and Rot/IF groups showed the same degree of weight loss when compared to control and Rot groups. An accelerating rotarod test revealed that only Rot/IF mice have a decreased ability to sustain the test at the higher speeds. Rot/IF group showed a more marked decrease of dopaminergic neurons and increase in alpha-synuclein accumulation with respect to Rot group in the substantia nigra (SN). Through lipidomics and metabolomics analyses, we found that in the SN of Rot/IF mice a significant elevation of excitatory amino acids, inflammatory lysophospholipids and sphingolipids occurred. Collectively, our data suggest that, when applied in combination with neurotoxin exposure, IF does not exert neuroprotective effects but rather exacerbate neuronal death by increasing the levels of excitatory amino acids and inflammatory lipids in association with altered brain membrane composition.